1987
DOI: 10.1111/j.1365-2605.1987.tb00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the accuracy of traditional sperm characteristics and adenosine triphosphate (ATP) in estimating the fertilizing potential of human semen in vivo

Abstract: Receiver operating characteristic curves and accuracy parameters were computed for traditional sperm characteristics (concentration, motility, morphology) and the number of peroxidase negative cells, and the concentration of adenosine triphosphate (ATP) in semen from populations of fertile and infertile men, and men who achieved a pregnancy after varicocele treatment. The percentage and concentration per millilitre of spermatozoa with rapid linear progressive motility, and the ATP concentration, provided the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 11 publications
2
28
1
2
Order By: Relevance
“…This was in contrast to the results of Comhaire et al [5] who found that higher ATP correlated with higher motility. According to Burger et al.…”
Section: Discussioncontrasting
confidence: 57%
“…This was in contrast to the results of Comhaire et al [5] who found that higher ATP correlated with higher motility. According to Burger et al.…”
Section: Discussioncontrasting
confidence: 57%
“…Indeed, a significant decrease in both sperm concentration and total sperm count, and a severe decline of rapid progressive motility (grade a) were observed in the two populations. Comhaire et al 33 postulate that the percentage of spermatozoa with grade 'a' motility is the strongest indicator of the potential for in vivo fertilizing capacity of semen. Our results would suggest that an increasing proportion of men in our region could be candidates for assisted medical procreation techniques over time.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular Ca 2+ has a profound negative impact of phosphotyrosine expression by mammalian spermatozoa by virtue of an associated decrease in intracellular ATP availability. Resolving the nature of the calciumdependent enzymes involved in ATP depletion may shed light on the etiology of male infertility given the association between defective sperm function and intracellular ATP content (Comhaire et al, 1987).…”
Section: Discussionmentioning
confidence: 99%